Body Composition and Physical Fitness Affect Central Hemodynamics in Young Children - Köchli, Sabrina; Deiseroth, Arne; Hauser, Christoph; Streese, Lukas; Schmidt-Trucksäss, Arno; Faude, Oliver; Hanssen, Henner (Frontiers in Pediatrics, 2021)
Objective: Central haemodynamics are related to cardiovascular (CV) outcomes in adults but associations with childhood CV risk remain unclear. The study aimed to investigate the association of obesity, physical activity and fitness with parameters of central pulse wave reflection in young prepubertal children. Methods: In this cross-sectional study, 1324 primary school children (aged 7.2±0.4 years) were screened for parameters of pulse wave reflection such as augmentation index (AIx), central pulse pressure (CPP), body mass index (BMI) and cardiorespiratory fitness (CRF) by standardized procedures for children. Results: Mean AIx and AIx@75 were 22.2±7.7% and 29.2±9.2%, respectively. With each unit increase of BMI, AIx (-0.226(-0.328;-0.125)%) and AIx@75 (-0.444(-0.660;-0.229)%) decreased whereas peak forward pulse wave increased (p<0.001). Increasing BMI was associated with higher CPP, but did not remain significant after adjustment for CRF and heart rate. One unit increase in CRF was associated with lower AIx@75 (-0.509(-0.844;-0.173)%, p=0.003) and lower reflection magnitude (RM:-0.559(-0.890;-0.227), p=0.001), independent of body weight and height. Girls had significantly higher AIx, AIx@75, peak backward pulse wave and RM compared to boys. Conclusion: Childhood obesity was associated with higher CPP but lower augmentation of the reflected pulse wave in children. Assessment of central blood pressures appears to be a valuable asset to childhood CV risk screening. The validity of augmentation indices during childhood development and the association with early vascular ageing in children need to be verified in long-term follow-up studies. Physical activity and fitness have the potential to improve vascular haemodynamics in susceptible children and thus counteract vascular ageing.